Levothyroxine Therapy in Elderly Patients With Hypothyroidism - Effraimidis, Grigoris; Watt, Torquil; Feldt-Rasmussen, Ulla (Frontiers in Endocrinology, 2021)
Treating overt hypothyroidism with levothyroxine (L-T4) can be more challenging in elderly patients, compared with young patients. The elderly population is growing, and increasing incidence and prevalence of hypothyroidism with age are observed globally. Elderly people have more comorbidities compared to young patients, complicating correct diagnosis and management of hypothyroidism. Most importantly, cardiovascular complications compromise the usual start dosage and upward titration of L-T4 due to higher risk of decompensating cardiac ischaemia and -function. It therefore takes more effort and care from the clinician, and the maintenance dose may have to be lower in order to avoid a cardiac incidence. On the other hand, L-T4 has a beneficial effect on cardiac function by increasing performance. The clinical challenge should not prevent treating with L-T4 should the patient develop e.g cardiac ischaemia. The endocrinologist is obliged to collaborate with the cardiologist on prophylactic cardiac measures by invasive cardiac surgery or medical therapy against cardiac ischaemic angina. This usually allows subsequent successful treatment. Management of mild (subclinical) hypothyroidism is even more complex. Prevalent comorbidities in the elderly complicate correct diagnosis, since many concomitant morbidities can result in non-thyroidal illness, resembling mild hypothyroidism both clinically and biochemically. The diagnosis is further complicated as methods for measuring thyroid function (thyrotropin and thyroxine) vary immensely according to methodology and background population. It is thus imperative to ensure a correct diagnosis by aetiology (e.g autoimmunity) before deciding to treat. Even then, there is controversy regarding whether or not treatment of such mild forms of hypothyroidism in elderly will improve mortality, morbidity and quality of life. This should be studied in large cohorts of patients in long-term placebo-controlled trials with clinically relevant outcomes. Other cases of hypothyroidism e.g. medications, iodine overload or hypothalamus-pituitary-hypothyroidism each pose specific challenges to management of hypothyroidism; these cases also have a higher frequency in the elderly. Finally, adherence to treatment is generally challenging. This is also the case in elderly patients, which may necessitate measuring thyroid hormones at individually tailored intervals, which is also important to avoid over-treatment with increased risk of cardiac morbidity and mortality, osteoporosis, cognitive dysfunction and muscle deficiency.